Multiobjective differential evolution algorithm-based sizing of a standalone photovoltaic water pumping system - Muhsen D.H.; Ghazali A.B.; Khatib T. (Elsevier Ltd, 2023)
Algorithms; Costs; Evolutionary algorithms; Flow of water; Life cycle; Meteorology; Multiobjective optimization; Optimization; Probability; Pumping plants; Pumps; Solar power generation; Differential Evolution; Lifecycle costs; Meteorological data; Multi-objective differential evolution algorithms; Objective functions; Photovoltaic; Photovoltaic water pumping; Solar waters; Loss of load probability